2017
DOI: 10.1111/bor.12238
|View full text |Cite
|
Sign up to set email alerts
|

Past changes of spring drought in the inner Tianshan Mountains, China, as recorded by tree rings

Abstract: Drought is a common natural disaster in arid Central Asia, and the severity and frequency of drought and other hydroclimatic events are critical to the region's ecology and its residents' livelihoods. In particular, water resource management requires reliable knowledge of climatic variability and annual and centennial drought patterns. In this paper, we establish a 587-year tree ring chronology using 215 Schrenk spruce (Picea schrenkiana Fisch. et Mey) samples and reconstruct a spring Palmer Drought Severity I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…12a shows that the reconstruction values were significantly correlated with the North Atlantic Oscillation Index in the summer (SNAO, Folland et al, 2009), with the high-frequency change in March to September (r = 0.221, p < 0.05, 1930 and the low-frequency change occurring with the 5-year moving average (r = 0.366, p < 0.01, 1930-2012). The same conclusion has been found in the reconstruction of precipitation over the last 300 years in the west-central Tianshan Mountains, the reconstruction of drought in the past 364 years in the central and western Tianshan Mountains, and the streamflow reconstruction of the eastern Tianshan Mountains over the past 330 years (Wang et al, 2015;Chen and Yuan, 2016;Zhang et al, 2017). The reconstruction results were correlated with the Western Pacific Oscillation Index (WPO, https://crudata.uea.ac.uk/cru/data/wpo/), with the highfrequency change in April to August (r = 0.331, p < 0.01, 1950-2012) and the low-frequency change occurring with the 5-year moving average (r = 0.528, p < 0.01, Fig.…”
Section: Relationship Between Reconstruction Results and External Envsupporting
confidence: 74%
See 1 more Smart Citation
“…12a shows that the reconstruction values were significantly correlated with the North Atlantic Oscillation Index in the summer (SNAO, Folland et al, 2009), with the high-frequency change in March to September (r = 0.221, p < 0.05, 1930 and the low-frequency change occurring with the 5-year moving average (r = 0.366, p < 0.01, 1930-2012). The same conclusion has been found in the reconstruction of precipitation over the last 300 years in the west-central Tianshan Mountains, the reconstruction of drought in the past 364 years in the central and western Tianshan Mountains, and the streamflow reconstruction of the eastern Tianshan Mountains over the past 330 years (Wang et al, 2015;Chen and Yuan, 2016;Zhang et al, 2017). The reconstruction results were correlated with the Western Pacific Oscillation Index (WPO, https://crudata.uea.ac.uk/cru/data/wpo/), with the highfrequency change in April to August (r = 0.331, p < 0.01, 1950-2012) and the low-frequency change occurring with the 5-year moving average (r = 0.528, p < 0.01, Fig.…”
Section: Relationship Between Reconstruction Results and External Envsupporting
confidence: 74%
“…(Wen et al, 2006;Chen et al, 2012a). The mean minimum temperature reconstruction had a good correspondence with the drought events in the Xinjiang region, and the values of the drought events were significantly higher than the average reconstructed temperatures, especially in some extreme drought years, such as 1775, 1919, and 1945(Chen et al, 2013Zhang et al, 2017). Radial growth of trees is also responsive to volcanic eruptions and temperature changes had been importantly affected by many upper westerly circulation and low latitude tropics massive volcanic eruptions in central Asia (Chen et al, 2012b).…”
Section: Reconstruction Of the Spatial Representation And Regional Comentioning
confidence: 97%
“…In previous dendroclimatological studies in the Tianshan Mountains, we found that long-term changes in moisture have a strong local character [7,9,10,26,38,39]. The consistency of the change decreases rapidly with increasing distance.…”
Section: Discussionmentioning
confidence: 57%
“…All pooled samples were grounded into powder in a ball mill (MM 400, Retsch GmbH, Germany), and the α cellulose was extracted using the method of Brendel et al [45]. This method has been widely used in dendroclimatology studies [34,35,46].…”
Section: Stable Carbon Isotopic Extractionmentioning
confidence: 99%
“…There are a large number of Schrenk spruce (Picea schrenkiana Fisch. et Mey) virgin forests in this region and this species has been shown to be suitable for dendrochronological study [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, few studies have discussed the relationship between C a , climate, radial growth, and iWUE in the Tianshan Mountains [39,40].…”
Section: Introductionmentioning
confidence: 99%